'Fundamentalism in African traditional religion': a reflection on some points for consideration - Sakuba, Xolani (Scriptura, 2008)
This article explores the possibility that, although there is no full-blown ‘African fundamentalism’, certain fundamentalist tendencies can be detected among adherents of African Traditional Religion. After a summary of typical features of ATR, two area are identified within which fundamentalist tendencies are manifested: the family or clan and public debates driven by (pan-)African nationalist movements or ethnic nationalism. In the latter case the tendencies are often seen purely political, but it is argued that in the African context there is no clear distinction between religion, culture and politics. Moreover, the colonial heritage colours the way in which fundamentalist tendencies are expressed in Africa. In each case various examples are given and assessed to determine whether the tendencies can be called fundamentalist. Finally, the question is asked whether there can be fundamentalism without a scripture. It is suggested that, since ATR has no scriptures, ancestors take the role of ultimate authority.
free
Keywords: Africa – Religion; Ancestors – Religious aspects; Fundamentalism; Pan-Africanism; State and religion; Tradition